TERSEMBUNYI DALAM KAIN: STUDI HISTORIS AKULTURASI ETNIS PANARAGAN DAN MADURA PADA PAKAIAN ADAT PENADON - Iqbal Rizki Sucahyo; Yuliati; Shafira Daniar Rahma Herlamb; Helen Aura Valentina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Panaragan ethnic in Ponorogo and Madura ethnic are two ethnic groups with famous cultures from the East Java. These two ethnic groups have many cultural similarities, especially traditional clothing that may have resulted by acculturation. Studies on the acculturation process is rarely discussed due to limited primary sources, but there are still several secondary sources that are worthy for considering. This study uses a historiography and guided by the aspect of cultural hybridity. The interaction between Ponorogo and Madura has occurred since Ponorogo was founded with a family relationship between the two ethnic. The development process of Reyog also influenced the formation of Penadon clothes. In addition, traditional Madurese clothing or several other regions are actually rooted in one concept of the Astronesian’s belief in viewing black as sacred color. However, each ethnic group has its own uniqueness that is different from other ethnic groups and different functions of clothing. The results of this study are useful for the next generation as a form of cultural appreciation that is not only limited to preservation but also the advancement of culture.